Kernel-like impurity detection according to colour band spectral image using GA/SVM. (11th June 2015) - Chen, F.; Chen, P.; Li, D.; Cheng, F.
Abstract : Kernel-like impurities (KLIs) have the similar colour, shape, texture and specific gravity with sound kernels. The amount of the KLIs is an important parameter for evaluating the quality of wheat. However, it is difficult to classify KLIs from sound kernels with normal methods because of these similar features. In this study, a machine vision system with a linear colour charged coupled device used to acquire images of kernels and a software package developed to extract various features from the images were used to classify 1169 sound kernels and 896 KLIs. Three methods—genetic algorithm (GA)/support vector machine (SVM), principal components analysis/SVM and linear discriminant analysis—were applied for the classification. The performance of GA/SVM for detecting KLIs was very outstanding, and the accuracy of testing sets could reach 99.34%. GA/SVM has the potential to improve the KLI classification accuracy in machine vision system. It is feasible to extract a small quantity of useful features without any extra image or data processing for online KLI classification.